1997
DOI: 10.1128/jvi.71.3.2233-2240.1997
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of defective viral genomes in peripheral blood mononuclear cells of human immunodeficiency virus type 1-infected individuals

Abstract: Human immunodeficiency virus type 1 (HIV-1) genomes present in peripheral blood mononuclear cells (PBMCs) of infected persons or in lymphocytes infected in vitro were studied by long-distance PCR (LD-PCR) using primers localized in the HIV-1 long terminal repeats. The full-length 9-kb DNA was the only LD-PCR product obtained in peripheral and cord blood lymphocytes from seronegative donors infected in vitro. However, a high proportion (27% to 66%) of distinct populations of extensively deleted HIV-1 genomes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
62
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(65 citation statements)
references
References 29 publications
3
62
0
Order By: Relevance
“…These deletions vary widely in length but typically encompass multiple viral genes (13)(14)(15)(16)22). Deletions likely arise during reverse transcription when the polymerase jumps to a homologous region on the same template during negative-strand synthesis, but other mechanisms may contribute (16,(22)(23)(24). Other less common defects include frameshift mutations and inverted segments of the HIV-1 genome inserted within a large multigenic deletion (14).…”
Section: Introductionmentioning
confidence: 99%
“…These deletions vary widely in length but typically encompass multiple viral genes (13)(14)(15)(16)22). Deletions likely arise during reverse transcription when the polymerase jumps to a homologous region on the same template during negative-strand synthesis, but other mechanisms may contribute (16,(22)(23)(24). Other less common defects include frameshift mutations and inverted segments of the HIV-1 genome inserted within a large multigenic deletion (14).…”
Section: Introductionmentioning
confidence: 99%
“…In spite of extensive investigations of the nef sequence heterogeneity, selective conservation of these regions during the disease progression in vivo has not been previously noted [33–35,39]. Since in these studies the nef gene was amplified directly from the patient plasma or the infected cells, it is likely that these nef sequences did not represent the replication‐competent virus [40–43]. Although these defective viruses may kill the infected cells, they do not produce progeny virions and thus do not contribute to the disease progression.…”
Section: Resultsmentioning
confidence: 98%
“…It is of note that a study has demonstrated that, in some patients who are receiving virally suppressive HAART with transient spikes of virus of 150 copies/mL in plasma, resistance mutations may develop [21]. Data from the aforementioned studies demonstrated that, although defective proviruses accumulate in CD4 ϩ T lymphocytes in vivo (i.e., "viral graveyard sequences") [22], replication-competent provirus still exists in resting CD4 ϩ T lymphocytes, which may hinder attempts at reducing the viral reservoir and may reseed the body with virus if HAART is discontinued. These possibilities, therefore, confound our attempts toward pharmacologically mediated virus eradication.…”
Section: Hiv-1 Latency In Resting Cd4 + T Lymphocytes In Vivomentioning
confidence: 99%